2001
DOI: 10.1002/smj.185
|View full text |Cite
|
Sign up to set email alerts
|

Finding the right mix: franchising, organizational learning, and chain performance

Abstract: Franchising provides an increasingly important vehicle for entrepreneurial wealth creation and accounts for a large and growing share of business in the retail and service sectors. Chains—which operate in dispersed markets—most frequently use this form of governance. These firms must balance the centralization and standardization required for efficiency with the adaptation needed for success in varied local markets. By adopting an organizational learning perspective, we argue that the mix of company‐owned and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
400
1
16

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(450 citation statements)
references
References 30 publications
20
400
1
16
Order By: Relevance
“…Thus, a disruption in the innovation activity of firms may force them to turn outward to external technology source. Nevertheless, distinctive knowledge bases of internal and external sources can be particularly valuable under conditions of technological uncertainty (Sorenson and Sorensen, 2001) and might be of use in creating knowledge complementarities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, a disruption in the innovation activity of firms may force them to turn outward to external technology source. Nevertheless, distinctive knowledge bases of internal and external sources can be particularly valuable under conditions of technological uncertainty (Sorenson and Sorensen, 2001) and might be of use in creating knowledge complementarities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Not surprisingly, knowledge flowed between the locations under one owner, but did not flow into the franchisor or other franchisee owners at nearly the same speed. Sorenson and Sorensen (2001) also found this lack of systems when evaluating the comparison between franchise and locally owned locations in the same market. They found that "chains also monitored franchisee behavior, but less stringently and less systematically" than company-owned locations (p. 715).…”
Section: Rq2 and H1a -H1gmentioning
confidence: 95%
“…Studies explored the development of knowledge within the franchise network and migration of that knowledge throughout the network both among the franchisees and between a franchisee and franchisor (Darr, Argote, & Epple, 1995;Hoy, 2008;Kalnin & Mayer, 2004;Knot & McKelvey, 1999;Lindblom & Tikkanen, 2010;Sorenson & Sorensen, 2001;Watson et al, 2005). These studies showed how information originates and flows throughout the network; however, the perception of a presence of the dimension of a learning organization across the franchise network is underexplored.…”
Section: Notementioning
confidence: 99%
“…Franchisors intangible assets are related to brand name and system specific know-how (Norton, 1988;Windsperger & Dant, 2006), while franchisees intangible assets are related to the local know-howcustomer service, quality control, human resource management, product innovation (Sorenson & Sorensen, 2001;Windsperger, 2001;Windsperger & Dant, 2006).…”
Section: Property Rights Theorymentioning
confidence: 99%